Discipline in the classroom (problems and solutions) (Journal Of Educational and Psychological Researches, 2018)
Research SummaryFirst: the problem of research and its importance      The teacher's success in facilitating the students' learning and growth according to the educational and educational goals set out, he must identify the problems of discipline of students in the classroom in terms of sources and reasons and types and methods of prevention and treatment and the teacher to remember that success in his teaching and instruction is not completed more fully once he has the information And knowledge of the subject of the lesson, but must understand the dynamics of the group (class group) and master the skills of classroom management, such as providing the psychological and social climate appropriate to the process of learning and the use of methods and methods of learning and education based on participation and cooperation and dialogue Consultation to reach the common goals of teaching and learning processes. For this arrogating the researcher to identify the discipline in class solutions and problemsSecond: The limits of research were limited to information that could achieve the research objectivesChapter II Research Methodology The researcher followed an analytical descriptive approach to identify problems and solutions of discipline within the classroomClass discipline conceptLearning environmentThe role of the teacher in controlling the learning environment?Strategies for solving classroom discipline problemsChapter III: This chapter contains a number of recommendations and proposals First: RecommendationsMinimize the use of corporal punishment, especially to the lowest degree possible. To give the student an opportunity to discourage bad behavior or direct him to do the right behavior to encourage and strengthen his direction immediately.Second: ProposalsPreparing a guide for the teacher to familiarize himself with the problems encountered during teaching and the strategy of solving them to achieve discipline class system